Pengaruh Penambahan Onggok terhadap Kecernaan Domba Ekor Tipis - Ma'ruf, A; Yakin, E A; Purwati, C S (Politeknik Negeri Lampung, 2025)
This study aims to determine the effect of adding cassava dregs in rations on nutrient consumption of Javanese thin-tailed sheep. This study was conducted from February to March 2024 at the Berkah Cempe farm, Baturetno district, Wonogiri Regency. The study used a completely randomized design with a one-way pattern consisting of 3 treatments and 4 replications. Treatment P1: 60% king grass + 40% concentrate + 0% cassava dregs, P2: 60% king grass + 40% concentrate + 10% cassava dregs, and P3: 60% king grass + 40% concentrate + 20% cassava dregs. The observation variables were dry matter digestibility, organic matter digestibility and crude protein digestibility. The results showed the highest average of dry matter digestibility, organic matter digestibility, and crude protein digestibility was P3 (60% king grass + 40% concentrate + 20% cassava dregs). The conclusion in this study was that the addition of cassava dregs up to 20% to Javanese thin-tailed sheep feed has a significant effect on dry matter digestibility, organic matter digestibility and crude protein digestibility.